Impaired fertility in mice deficient for the testicular germ-cell protease PC4 - Mbikay, Majambu (The National Academy of Sciences of the USA, 1997)
PC4 is a member of the proprotein convertase family of serine proteases implicated in the processing of a variety of polypeptides including prohormones, proneuropeptides, and cell surface proteins. In rodents, PC4 transcripts have been detected in spermatocytes and round spermatids exclusively, suggesting a reproductive function for this enzyme. In an effort to elucidate this function, we have disrupted its locus (Pcsk4) by homologous recombination in embryonic stem cells and have produced mice carrying the mutation. In intercrosses of heterozygous mutant mice, there was low transmission of the mutant Pcsk4 allele to the progeny, resulting in lower than expected incidence of heterozygosity and null homozygosity. The in vivo fertility of homozygous mutant males was severely impaired in the absence of any evident spermatogenic abnormality. In vitro, the fertilizing ability of Pcsk4 null spermatozoa was also found to be significantly reduced. Moreover, eggs fertilized by these spermatozoa failed to grow to the blastocyst stage. These results suggest that PC4 in the male may be important for achieving fertilization and for supporting early embryonic development in mice.